Integration of HIV, Hepatitis B, and C, and sexually transmitted infections services: A scoping review of the benefits and challenges - Parya Jangipour Afshar; Vahid Yazdi-Feyzabadi; Zahra Abdolahinia; AliAkbar Haghdoost; Jaason M. Geerts; Reza Goudarzi; Katayoun Tayeri; Babak Eshrati; Hamid Sharifi (PLoS ONE, 2026)
Background Integrating clinical programs and services is a cost-effective approach that can improve health and system outcomes. This review aimed to provide an overview of the benefits and challenges of integrated programs for HIV, hepatitis B and C, and STI services worldwide and provide recommendations for research and practice. Methods This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. We searched electronic databases PubMed, Scopus, and Web of Science until May 2025 to extract relevant studies. Additionally, we reviewed reputable grey literature sources, such as WHO and UNAIDS, and references from included publications for further relevant articles. Studies that had eligible criteria were included. We applied a narrative approach to report the findings through an inductive approach. Results Out of 19,516 initially identified studies, 118 were selected. The benefits and challenges of integration were classified into six categories: integrated service delivery, medical information and technology, human resources, health outcomes, collaboration and partnerships, and financial/physical resources. The significant benefits of these classifications include improved health outcomes, cost-effectiveness, enhanced efficiency, prevention of transmission, use of comprehensive care, reduction of time for receiving necessary services, increased knowledge and awareness, and improved cooperation. However, integration has some challenges, including the need for sufficient infrastructure, budget, human resources, and the potential for increased stress and work pressure on employees. Conclusions Prioritizing health is key to national development, requiring policies and resources for cost-effective patient and community benefits. This scoping review highlights the feasibility and advantages of integrating services for HIV, hepatitis B and C, and STIs. Our findings strongly support policymakers in prioritizing the planning and implementation of these integrated programs. An evidence-informed integration framework is needed to guide these actions effectively.